2020
DOI: 10.1177/1533033820947759
|View full text |Cite
|
Sign up to set email alerts
|

Two-Level Factorial Pre-TomoBreast Pilot Study of Tomotherapy and Conventional Radiotherapy in Breast Cancer: Post Hoc Utility of a Mean Absolute Dose Deviation Penalty Score

Abstract: Background: A 2-level factorial pilot study was conducted in 2007 just before starting a randomized clinical trial comparing tomotherapy and conventional radiotherapy (CR) to reduce cardiac and pulmonary adverse effects in breast cancer, considering tumor laterality (left/right), target volume (with/without nodal irradiation), surgery (tumorectomy/mastectomy), and patient position (prone/supine). The study was revisited using a penalty score based on the recently developed mean absolute dose deviation (MADD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Counterbalancing the limitations, the study argues against practice bounds to the development of breast radiotherapy. Conventional radiotherapy of the breast is still the preferred technique, advanced radiation is discouraged from reimbursement [ 9 ]. The present study is the counterpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counterbalancing the limitations, the study argues against practice bounds to the development of breast radiotherapy. Conventional radiotherapy of the breast is still the preferred technique, advanced radiation is discouraged from reimbursement [ 9 ]. The present study is the counterpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated imaging improves the accuracy of the treatment, allowing to treat tumors yet sparing critical structures. TomoBreast is a randomized clinical trial that investigates whether the technical advantage of tomotherapy translates into a substantial reduction of pulmonary and cardiac toxicities, as compared with conventional radiotherapy [9]. Previous reports of the trial have shown that tomotherapy improved the homogeneity of the dose to targets, decreased the dose to the heart and ipsilateral lung, and reduced the pooled all-grades lung-heart toxicity [10].…”
Section: Introductionmentioning
confidence: 99%
“…A good number of technical procedures seeking to find the best trade-off between side effects and tumor control are actively pursued [15][16][17][18][19][20]. This subject matter is even more relevant when considering treatment optimization for left-sided breast cancer [21][22][23][24][25][26][27][28]. A prone setup has been advocated to spare the left lung and the heart when irradiating such patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the impact of respiratory movement on the target, the daily radiation positioning deviation should be considered, although some radiation oncologists suggest that daily indoor CT scans, repositioning, and repeat planning of radiotherapy can reduce the severity of the deviation ( 58 ). However, there is no consensus on how much of the daily target deviation is acceptable, even though most radiation oncologists currently consider the deviation of conventional photon radiotherapy to be within the acceptable range of ± 3 mm ( 59 , 60 ). How this is not necessarily the case for protons, where small shifts may cause larger deviations in dose distribution.…”
Section: Discussionmentioning
confidence: 99%